RESEARCH OF THE CUTTING MECHANISM DRIVE FOR UNLOADING SILAGE FROMTRENCH STORES - RUTKEVYCH, VOLODYMYR; SHARGORODSKIY, SERHIY; OSTAPENKO, ALEXEI (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The issue of efficiency improvement is under consideration unloading of stem fodder from trench storages, by development of the cutting mechanism to the front loader and justification of its drive. The technical solution of the drive i provided and theoretically substantiated cutting mechanism to the front loader. The advantages and disadvantages of the existing drives of mechanisms for cutting and unloading are indicated stem fodder from trench storages. It is noted that significant unbalanced forces of inertia arising during the operation of the knife of the cutting mechanism cause vibration of the working body and the entire loader. Reduction of inertial forces is possible when additional counterweights are installed on the links of the drive mechanism of the cutting body, but this will lead to a significant increase in pressure in the kinematic pairs, which reduces the durability and reliability of the knife drive mechanism. Proposed options for increasing the efficiency of the drive cutting mechanism. It is necessary to lighten the mass of the structure use the minimum possible number of links, as well as for increasing reliability it is necessary to get rid of flexible connections such as chain and belt transmissions. You can also increase the efficiency of the drive of the cutting mechanism by simultaneously moving two knives. A very important task is to create a balanced mechanism for the maximum reduction of the vibration of the notch mechanism with a front loader and premature wear of parts. Therefore, the most effective use of self-balancing mechanisms. Based on theoretical studies of drive kinematics and dynamics of the cutting mechanism, the development trends of this drive are outlined, which will ensure an improvement in the quality of execution by the working body of the technological process of removing fodder from trench storages and reduce dynamic load on the drive.